Tantangan Pelaksanaan Program Prevention Of Mother To Child Transmission (PMTCT): Systematic Review - Nimas Ayu Lestari Nurjanah; Tri Yunis Miko Wahyono (Sekolah Vokasi Universitas Gadjah Mada, 2019)
Background: HIV / AIDS is still a global health problem which needs to be addressed including prevention of HIV / AIDS transmission from mother to child. Prevention of transmission is carried out by implementing the Prevention of Mother to Child Transmission or PMTCT program. The PMTCT program is considered successful in reducing the risk of mother-to-child transmission, but this has not been done well and thoroughly, various kinds of challenges have occurred in the implementation of the PMTCT program.Objective: To know the challenges that occur in implementing the PMTCT programMethod: This study uses a systematic review based on Preferred Reporting Items For Systematic Reviews & Meta-Analyzes (PRISMA) to identify all the literature published using relevant keywords.Results: challenges in implementing the PMTCT program are the lack of information on HIV treatment, lack of family support, the heavy workload experienced by health workers and the limited availability of HIV testing equipment and drug stocks.Conclusion: The success of efforts to prevent HIV / AIDS transmission from mother to child does not depend on one party only, but involves several parties, the active role of health workers in providing education and information about HIV / AIDS to mothers and their families is not enough but must be added with active roles and support from family members to HIV mothers as the primary motivator for good behavior in accordance with the guidelines for PMTCT.